In vitro effect of 5-fluorouracil and paclitaxel on Echinococcus granulosus larvae and cells - Pensel, Patricia Eugenia (2014)
Human cystic echinococcosis is a zoonosis caused by the metacestode stage of the tapeworm Echinococcus granulosus. Although benzimidazole compounds such as albendazole and mebendazole have been the cornerstone of chemotherapy for the disease, there is often no complete recovery after treatment. Hence, in searching for novel treatment options, we examined the in vitro efficacies of 5-fluorouracil (5-FU) and paclitaxel (PTX) against E. granulosus germinal cells, protoscoleces and cysts. 5-FU or PTX inhibited the growth of E. granulosus cells in a time dependent manner. Although both treatments had a protoscolicidal effect, 5-FU had a considerably stronger effect than PTX. 5-FU produced a dose- and time-dependent effect, provoking the complete loss of viability after 24 days of incubation. Moreover, cysts did not develop following the inoculation of treated protoscoleces into mice. The loss of viability was slower in PTX treated protoscoleces, reaching to approximately 60% after 30 days. The results of the in vitro treatment with 5-FU and PTX were similar in secondary murine cysts. The employment of SEM and TEM allowed us to examine, at an ultrastructural level, the effects induced by 5-FU and PTX on E. granulosus germinal cells, protoscoleces and murine cysts. In conclusion, the data obtained clearly demonstrated that 5-FU and PTX at clinically achievable concentrations inhibit the survival of larval cells, protoscoleces and metacestodes. In vivo studies to test the antiparasitic activities of 5-FU and PTX are currently being undertaken on the murine model of cystic echinococcosis.